2019
DOI: 10.1111/phn.12594
|View full text |Cite
|
Sign up to set email alerts
|

Intentionality in reducing health disparities: Caring as connection

Abstract: Objective Inadequate health care quality may contribute to Native American health disparities through racial/ethnic discrimination by health care professionals. Nursing approaches to relationships and caring offer a means to understand health disparities through an unconventional lens. The study objective was to examine health disparities within the context of patient/nurse relationships. Design A descriptive‐qualitative method guided data collection and analysis. Eleven nurses who serve Native Americans were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Native American participants valued and acknowledged the nursing roles of advocacy, support, and advice. This is consistent with research findings indicating that nurses who work with Native American clients report the importance of shared patient-nurse values, for example, connecting and advocacy, in the context of Native American health (Purtzer & Thomas, 2019). Clearly, both Native Americans and nurses express value for advocacy.…”
Section: Subtheme 2 Native American Advice To Other Native Americasupporting
confidence: 87%
See 2 more Smart Citations
“…Native American participants valued and acknowledged the nursing roles of advocacy, support, and advice. This is consistent with research findings indicating that nurses who work with Native American clients report the importance of shared patient-nurse values, for example, connecting and advocacy, in the context of Native American health (Purtzer & Thomas, 2019). Clearly, both Native Americans and nurses express value for advocacy.…”
Section: Subtheme 2 Native American Advice To Other Native Americasupporting
confidence: 87%
“…Nurses can enrich cultural competence by connecting at the point-ofcare through authentic relationships and focusing on patient's guidance and shared learning. Participant suggestions are supported by research that revealed the need for cultural-competence education that focus on nurse awareness, critical self-reflection, implicit bias and deeply held assumptions, and racism (Purtzer & Thomas, 2019).…”
Section: Subtheme 2 Native American Advice To Other Native Americamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some healthcare providers concurred that they viewed minorities as more intimidating due to their appearance which limited their effort to engage with them or offer therapy [ 8 , 42 ]. They acknowledged their failure to understand the differing needs of minority patients to administer individualized care [ 8 , 35 , 36 , 40 ]. Instances of overt racism were also reported by providers who observed that racial minorities were sometimes referred to using racially derogatory labels [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Providers frequently labelled minority patients as less compliant with treatment and felt that they lacked ownership over their health [ 27 , 35 , 43 , 45 ]. These providers tended to blame health disparities [ 27 , 36 , 45 ], or unsuccessful treatments [ 41 ], on minority patients’ poor behaviours, instead of unequal treatment arising from racism [ 35 ]. Some providers stated that they treated all patients equally [ 33 , 36 ], while others perceived minority patients to be oversensitive, holding the view that these patients misinterpret innocent health encounters as racist due to their past experiences of racism [ 26 , 43 ].…”
Section: Resultsmentioning
confidence: 99%